2014
DOI: 10.1128/aac.02494-13
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Nucleotide Sequence of the Carbapenem Resistance-Conferring Conjugative Plasmid pLD209 from a Pseudomonas putida Clinical Strain Reveals a Chimeric Design Formed by Modules Derived from Both Environmental and Clinical Bacteria

Abstract: The complete sequence of the carbapenem-resistance-conferring conjugative plasmid pLD209 from a Pseudomonas putida clinical strain is presented. pLD209 is formed by 3 well-defined regions: an adaptability module encompassing a Tn402-like class 1 integron of clinical origin containing bla VIM-2 and aacA4 gene cassettes, partitioning and transfer modules, and a replication module derived from plasmids of environmental bacteria. pLD209 is thus a mosaic of modules originating in both the clinical and environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
(59 reference statements)
2
23
0
Order By: Relevance
“…Mobile genetic elements similar to those of Salmonella found in our P. aeruginosa strain have also been identified in the chromosome of Acinetobacter baumannii (43). Our finding raises concerns about recombination events between bacterial species of diverse clinical, animal, and environmental origins that may result in the propagation of antibiotic resistance determinants (44). Salmonella enterica carrying the VIM-2 MBL has been detected in Morocco, where the multidrug-resistant (MDR) S. enterica serovar Kentucky is prevalent (45).…”
Section: Discussionmentioning
confidence: 82%
“…Mobile genetic elements similar to those of Salmonella found in our P. aeruginosa strain have also been identified in the chromosome of Acinetobacter baumannii (43). Our finding raises concerns about recombination events between bacterial species of diverse clinical, animal, and environmental origins that may result in the propagation of antibiotic resistance determinants (44). Salmonella enterica carrying the VIM-2 MBL has been detected in Morocco, where the multidrug-resistant (MDR) S. enterica serovar Kentucky is prevalent (45).…”
Section: Discussionmentioning
confidence: 82%
“…The sequence of pKF715D was essentially identical (97%–100%) to that of plasmid pLD209 from P. putida strain LD209 (Marchiaro et al ., ) and plasmid pMRVIM0812 from Pseudomonas sp. MRSN12121 (NZ_CP010893.1).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that pDCPR1 is identical (except for 2 nucleotides [nt]) to part of pLD209 (KF840720) (9), including the replicase gene (repA), the partitioning system genes (trfB, parA, and parB), the Tn402-like class 1 integron harboring a bla VIM-2 gene cassette, and genes encoding several hypothetical proteins. Because only genes involved in conjugal transfer and virulence from pLD209 (20,221 bp) are deleted in pDCPR1 (Fig.…”
mentioning
confidence: 92%